The Role of Educational Science in Professional Knowledge: Student Teachers’ Reflections - Heikkilä, Mirva; Mankki, Ville; Iiskala, Tuike; Mikkilä-Erdmann, Mirjamaija (Oslo Metropolitan University - Storbyuniversitetet, 2026)
The significance of theoretical knowledge for professional practice is widely acknowledged, but how students in professional education construct meanings of their major subject remains understudied. This study examined how primary student teachers reflect on the role of educational science in their professional knowledge. Textual data were collected after their first practicum in a Finnish primary teacher education programme. Discourse analysis identified four discourses. In the discourse of depth, educational science enabled a thorough understanding of pupils. In the discourse of multifacetedness, simultaneous consideration of multiple aspects of teaching was evident. In the discourse of topicality, teachers could stay updated regarding the knowledge society through educational science. The discourse of systemicity underscored the contribution of educational science to societal progress. This study provides a better understanding of student teachers’ professional knowledge in curriculum development and programme design within teacher education.